Role of Cardiorespiratory Fitness, Aerobic, Exercise and Sports Participation in Female Cognition: A Scoping Review - Vinicius Muller Reis Weber; Marcos Roberto Queiroga; Jessica L. Puranda; Kevin Semeniuk; Meaghan Lindsay Macdonald; Diego Bessa Dantas; Danilo Fernandes da Silva; Kristi Bree Adamo (SpringerOpen, 2024)
Abstract Background The impact of cardiorespiratory fitness (CRF) on cognition is thought to be mediated by brain-derived neurotrophic factor. Aerobic exercise can increase CRF through various activities, including sports participation. The relationship between these factors in females has yet to be elucidated. Objective This review aims to map the current literature on the effects of aerobic exercise, sports participation, and CRF in healthy adult females, with sub-topics of pregnancy and menstrual cycle periodicity. Methods A scoping review of the literature was conducted following PRISMA guidelines and the PCC mnemonic (population, concept, and context). The following five databases were screened: CINAHL, Medline, Web of Science, SPORTDiscus, and Scopus. Eligible articles included healthy adult females, investigated aerobic exercise, sports participation or CRF, and linked outcomes to cognition. Data from included manuscripts was extracted and analyzed. Two sub-population groupings (pregnant individuals and menstrual cycle) were established to further aid the interpretation of the findings. Results Of the 300 titles and abstracts screened, 74 were eligible for full-text screening, and 28 were included in the scoping review. Of the 28 included, 14 did not control for or report on menstrual cycle phase or sex hormones. Conclusion This scoping review found an inverse 'U' relationship between aerobic exercise and cognition, demonstrating an optimal dose of aerobic exercise to benefit cognitive functions. As estrogen may impact the relationship between CRF and neural growth factors, more research is needed on this pathway, independent of the menstrual cycle, to determine potential beneficial effects. It is currently unknown whether sports participation can independently impact cognition.